STUDI PENGEMBANGAN INSTRUMEN EDUKASI UNTUK MENURUNKAN RISIKO PCOS (Polycystic Ovary Syndrome) PADA WANITA DENGAN OBESITAS - Ratna Widyasari; Adhisty Kharisma Justicia; Pinda Hutajulu (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Women with obesity would experience an increase in lipid. These lipids would be accumulated in the visceral part of the body caused anovulation that is part of the menstrual disorder called polycystic ovary syndrome (PCOS). This study aims to know factors that could affect obese women to change their lifestyle and to develop an instrument to educate obese women to decrease the risk of PCOS. This study consisted of three steps. In the first step, the obese woman was evaluated qualitatively using semi-structured interviews to know their education needs. In the second step, the education instrument was developed based on their education need. In the third step, the instrument education that had been developed was evaluated. The result showed that the kind of factors affecting obese women to change lifestyle was patient inside-factors and patient outside-factor (environment). Most of the patients had low knowledge about the disease and the cure causing misperception and uncompliance. Therefore, the education instrument was developed using the booklet. The result of the evaluation instrument showed that the booklet that had been developed could increase patient knowledge o change patient uncompliance behavior.